An Illustrated Key of Pyrgomorphidae (Orthoptera: Caelifera) of the Indian Subcontinent Region - Zahid, Sundus; Mariño-Pérez, Ricardo; Amehmood, Sardar Azhar; Muhammad, Kushi; Song, Hojun (Zootaxa, 2020)
The Indian subcontinent is known to harbor a high level of insect biodiversity and endemism, but the grasshopper fauna in this region is poorly understood, in part due to the lack of appropriate taxonomic resources. Based on detailed examinations of museum specimens and high-resolution digital images, we have produced an illustrated key to 21 Pyrgomorphidae genera known from the Indian subcontinent. This new identification key will become a useful tool for increasing our knowledge on the taxonomy of grasshoppers in this important biogeographic region.